Factors associated with spontaneous HBsAg clearance in chronic hepatitis B patients followed at a university hospital - Ferreira, Sandro C; Chachá, Silvana G F; Souza, Fernanda F; Teixeira, Andreza C; Santana, Rodrigo C; Villanova, Márcia G; Zucoloto, Sérgio; Ramalho, Leandra N; Perdoná, Gleici S C; Passos, Afonso D C; Martinelli, Ana L C (Annals of hepatology, 2014)
Few studies have evaluated the factors involved in the spontaneous HBsAg seroclearance in patients with chronic hepatitis B (HBV) followed up on a long-term basis from areas with a low prevalence of HBV infection. We aimed to determine the rate of spontaneous HBsAg seroclearance and the factors related to it in patients with chronic HBV infection followed up at the Hepatitis Outpatient Clinic of HCFMRP from 1992-2008. A total of 548 patients with chronic HBV infection (366 with chronic hepatitis B and 182 inactive carriers) were followed for 15 years and 9 months with an annual measurement of HBV-DNA, ALT, AST and GGT (average of 4 annual determinations) and serology (HBsAg, HBeAg, Anti-HBeAg and Anti-HBsAg). Spontaneous HBsAg seroclearance occurred in 40 patients (7.3%) with a mean age of 46.0 ± 14.4 years, corresponding to an annual rate of 0.7%.The factors related to spontaneous HBsAg seroclearance were inactive carrier status (67.5 vs. 32.5%, p = 0.000191) and age of more than 40 years (p = 0.0007). There was no difference in the rate of spontaneous HBsAg seroclearance when comparing males and females (p = 0.383). Patients with spontaneous HBsAg seroclearance did not progress to more severe forms of the disease during follow-up. Spontaneous HBsAg seroclearance has a favorable long-term prognosis in patients with chronic HBV infection. HBsAg seroclearance occurred at rates compatible with low prevalence areas and was associated with low serum HBV-DNA levels and an age older than 40 years.